Rapid Screening and Estimation of Binding Constants for Interactions of Fe3+ with Two Metalloproteins, Apotransferrin and Transferrin, Using Affinity Mode of Capillary Electrophoresis - Al Bratty, Mohammed; Alhazmi, Hassan A.; Javed, Sadique A.; Rehman, Zia Ur; Najmi, Asim; El-Sharkawy, Karam A. (Journal of Spectroscopy, 2021)
The interaction behavior of Fe3+ with transferrin and apotransferrin (iron-free form) was investigated in this study using affinity capillary electrophoresis. Change in the mass and charge of protein upon binding to the metal ion in the capillary tube led to variation in its migration time and was used to measure the noncovalent binding interactions by fast screening method. Acetanilide was used as the electroosmotic flow (EOF) marker to avoid possible errors due to the change in EOF during the experiment. The binding results were calculated from the mobility ratios of protein (Ri) and EOF marker (Rf) using the formula (Ri − Rf)/Rf or ∆R/Rf. For more comprehensive understanding, the kinetics of the interaction was studied and binding constants were calculated. Results showed that the Fe3+ displayed insignificant interaction with both proteins at lower metal ion concentrations (5–25 μmol/mL). However, transferrin exhibited significant interactions with the metal ion at 50 and 100 μmol/mL (ΔR/Rf = 0.0114 and 0.0201, resp.) concentrations and apotransferrin showed strong binding interactions (ΔR/Rf = −0.0254 and 0.0205, resp.) at relatively higher Fe3+ concentrations of 100 and 250 μmol/mL. The binding constants of 18.968 mmol−1 and −13.603 mmol−1 were recorded for Fe3+ interaction with transferrin and apotransferrin, respectively, showing significant interactions. Different binding patterns of Fe3+ with both proteins might be attributed to the fact that the iron-binding sites in transferrin have already been occupied, which was not the case in apotransferrin. The present study may be used as a reference for the investigation of protein-metal ion, drug-protein, drug-metal ion, and enzyme-metal ion interactions and may be helpful to provide preliminary insight into the new metal-based drug development.